2014
DOI: 10.1007/s00382-014-2343-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of seasonal prediction of East Asian summer rainfall related to western tropical Pacific convection

Abstract: approach using the cross-validated EARI from the individual models and their MME. The results show that the rainfalls reconstructed from simulations capture the general features of observed precipitation in East Asia quite well. This study convincingly demonstrates that rainfall prediction skill is considerably improved by using a hybrid dynamical-statistical approach compared to the dynamical forecast alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Particularly, climate prediction over inland continental regions such as Mongolia is one of the most challenging issues for state-of-the-art meteorology due to the limitations of current observation that hinder our understanding of the interaction between land surface and atmosphere and due to the difficulties in modelling the complex and inhomogeneous distribution of the terrestrial surface in detail. Thus, in spite of their relatively low climate prediction skill over continents, state-of-the-art CGCMs are still widely used for seasonal forecasting in many meteorological research centres and laboratories, such as the National Centers for Environmental Prediction (NCEP; Toth et al, 2001), the European Centre for Medium-Range Weather Forecast (ECMWF; Anderson et al, 2007), the Asia-Pacific Economic Cooperation Climate Center (APCC; Lee et al, 2013;Lee et al, 2014) and Pusan National University (PNU; Sun and Ahn, 2014;Kim and Ahn, 2015). Thus, in spite of their relatively low climate prediction skill over continents, state-of-the-art CGCMs are still widely used for seasonal forecasting in many meteorological research centres and laboratories, such as the National Centers for Environmental Prediction (NCEP; Toth et al, 2001), the European Centre for Medium-Range Weather Forecast (ECMWF; Anderson et al, 2007), the Asia-Pacific Economic Cooperation Climate Center (APCC; Lee et al, 2013;Lee et al, 2014) and Pusan National University (PNU; Sun and Ahn, 2014;Kim and Ahn, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, climate prediction over inland continental regions such as Mongolia is one of the most challenging issues for state-of-the-art meteorology due to the limitations of current observation that hinder our understanding of the interaction between land surface and atmosphere and due to the difficulties in modelling the complex and inhomogeneous distribution of the terrestrial surface in detail. Thus, in spite of their relatively low climate prediction skill over continents, state-of-the-art CGCMs are still widely used for seasonal forecasting in many meteorological research centres and laboratories, such as the National Centers for Environmental Prediction (NCEP; Toth et al, 2001), the European Centre for Medium-Range Weather Forecast (ECMWF; Anderson et al, 2007), the Asia-Pacific Economic Cooperation Climate Center (APCC; Lee et al, 2013;Lee et al, 2014) and Pusan National University (PNU; Sun and Ahn, 2014;Kim and Ahn, 2015). Thus, in spite of their relatively low climate prediction skill over continents, state-of-the-art CGCMs are still widely used for seasonal forecasting in many meteorological research centres and laboratories, such as the National Centers for Environmental Prediction (NCEP; Toth et al, 2001), the European Centre for Medium-Range Weather Forecast (ECMWF; Anderson et al, 2007), the Asia-Pacific Economic Cooperation Climate Center (APCC; Lee et al, 2013;Lee et al, 2014) and Pusan National University (PNU; Sun and Ahn, 2014;Kim and Ahn, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Meehl (1995) claimed that the coupled general circulation model (CGCM) is the ultimate tool for predicting the longterm weather and climate. Thus, in spite of their relatively low climate prediction skill over continents, state-of-the-art CGCMs are still widely used for seasonal forecasting in many meteorological research centres and laboratories, such as the National Centers for Environmental Prediction (NCEP; Toth et al, 2001), the European Centre for Medium-Range Weather Forecast (ECMWF; Anderson et al, 2007), the Asia-Pacific Economic Cooperation Climate Center (APCC; Lee et al, 2013;Lee et al, 2014) and Pusan National University (PNU; Sun and Ahn, 2014;Kim and Ahn, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To improve rainfall prediction over EA, multi-model ensemble (MME) predictions have been conducted (Wang et al 2009, Lee et al 2015. Based on evaluation of the MME seasonal hindcasts performed by 14 climate models that participate in the Climate Prediction and its Application to Society (CliPAS) project and 6 models from the DEMETER project, Wang et al (2009) concluded that forecast of monsoon precipitation remains a major challenge and the seasonal rainfall predictions over land and during local summer have little skill.…”
Section: Introductionmentioning
confidence: 99%
“…Based on evaluation of the MME seasonal hindcasts performed by 14 climate models that participate in the Climate Prediction and its Application to Society (CliPAS) project and 6 models from the DEMETER project, Wang et al (2009) concluded that forecast of monsoon precipitation remains a major challenge and the seasonal rainfall predictions over land and during local summer have little skill. Lee et al (2015) added downscaling methods to CilPAS prediction data in order to enhance prediction skill but there is no considerable improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have assessed the deterministic skills of different MME systems in historical predictions of the WNP‐EASM variability [e.g., Kang and Shukla , ; Wang et al , ; Chowdary et al , ; Lee et al , , , ; Li et al , ; Tang et al , ; Min et al , ; Ma et al , ]. The results from these studies indeed indicate that some benefit could be received from compositing single‐model ensembles (SMEs), but this benefit is sometimes cast into doubt by the fact that the MME does not always beat the best SME [ Kang and Shukla , ; Lee et al , ].…”
Section: Introductionmentioning
confidence: 99%